A Fatal Breakthrough COVID-19 Case Following Bendamustine-Rituximab Therapy. (August 2022) - Kamegai, Kohei; Iwamoto, Noriko; Togano, Tomiteru; Maeda, Kenji; Takamatsu, Yuki; Miyazato, Yusuke; Ishikane, Masahiro; Mizokami, Masashi; Sugiyama, Masaya; Iida, Shun; Miyamoto, Sho; Suzuki, Tadaki; et al.
Highlights: We report a fatal case of breakthrough infection with the SARS-CoV-2 Delta variant after the first vaccination course. Patients with hematologic malignancies are vulnerable to COVID-19 viral infection. Surveillance of mixed alleles could help detect unknown aggravating factors. Abstract: Although messenger ribonucleic acid vaccines are substantially effective toward SARS-CoV-2 infection, patients with hematologic malignancies are still prone to the virus. Herein, we report a fatal case of breakthrough SARS-CoV-2 Delta variant infection in a patient with mucosa-associated lymphoid tissue lymphoma with remission by bendamustine-rituximab (BR) therapy completed a year ago. The serologic study revealed impaired responsiveness toward vaccines and prolonged high viral load after infection. BR therapy seemingly induced an immune escape. Prevention and treatment strategies for such vulnerable patients should be clarified immediately.